Manajemen Waktu Pembelajaran Daring Di Masa Pandemi Covid-19 Pada TK Dharma Wanita 1 Baleturi - Agus Miftakus Surur; Ana Ulin Nadhirin (UIN Sultan Maulana Hasanuddin Banten, 2020)
This study aims to determine the time management of online learning in Kindergarten (TK) Dharma Wanita 1 Balleturi. The importance of learning time management is because it has many impacts such as having clear priorities, reducing delays, being on time in doing work so that it can increase satisfaction in doing tasks, having the ability to keep concentrating on tasks so as to increase productivity, and being able to practice disciplinary habits for this. -that relates to time so that the task will be carried out more efficiently. This research is a qualitative research, using data collection techniques such as observation, interviews, and documentation. The result of this research is that the fulfillment of aspects of time management can assist in the management of the online learning process. These aspects are setting goals, setting priorities, setting schedules, being assertive, being assertive, avoiding procrastination, minimizing wasted time, and controlling time. Keywords: time management; online learning; kindergarten; dharma wanita References Abdillah, L. A., Hasibuan, A., Purba, S., Tjiptadi, D. D., Sudarmanto, E., Solissa, F., Putra, A. H. P. K., Mistriani, N., Simarmata, H. M. P., Manuhutu, M. A., & Salman. (2020). Human Capital Management. Yayasan Kita Menulis. Al Amin, M. N. K. (2020). Menakar Nilai Kemanfaatan Penangguhan Walimat Al-‘Ursy Di Masa Darurat COVID-19 Melalui Analisis Sadd Adz-Dzari’ah. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 27–38. https://doi.org/10.47200/ulumuddin.v10i1.381 Bahri, S. (2019). Urgensi Strategi Pembelajaran Karakter Pada Anak Usia Dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(2), 75–86. Duraisy, B. R. (n.d.). Manajemen Waktu (Konsep dan Strategi). Fitrah, M., & Luthfiyah. (2018). Metodologi penelitian: penelitian kualitatif, tindakan kelas & studi kasus. CV Jejak (Jejak Publisher). Forsyth, P. (2009). Janganlah sia-siakan waktumu. Grara Ilmu. Gea, A. A. (2014). Time Management: Menggunakan Waktu Secara Efektif Dan Efisien. HUMANIORA, 5(2). Gheytasia, M., Azizifara, A., & Gowhary, H. (2015). The Effect of Smartphone on the Redial Comprehension Profiency of Iranian EFL Learners. GlobELT: An International Conference on Teaching and Learning English as an Additional Language, Antalya - Turkey. Ginting, D. (2020). SUPERVISOR 4.0: Essential Points. Desmon Ginting Academy. Hermansyah, Mujiono, Budiastuti, L. K. S., & Warohman. (2009). Modul Pengembangan Diri Melalui Layanan Bimbingan dan Konseling SMK. Paramitha Publishing. Hernimawati. (2018). Model Implementasi Kebijakan Penataan Reklame. Jakad Media Publishing. Moleong, L. J. (2011). Metodologi Penelitian Kualitatif. Remaja Rosda Karya. Musaropah, U. (2016). Pemberdayaan Masyarakat Dalam Penyelenggaraan Pendidikan Anak Usia Dini Berbasis Pesantren. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(2), 177–185. Najib, M. (2018). Model Manajemen PAUD Berdaya Saing Studi Pada Lembaga PAUD Islam Terpadu Al-Ikhlas Bumiayu Kabupaten Brebes. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 125–136. Nurmala, I. (2020). Mewujudkan Remaja Sehat Fisik, Mental dan Sosial: (Model Intervensi Health Educator for Youth). Airlangga University Press. Pandoman, A. (2020). Analisis Quietus Politik Terhadap Upaya Pemerintah Menangani Wabah Covid-19 Pasca Deklarasi Public Health Emergency Of International Concern (PHEIC). Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 1–12. https://doi.org/10.47200/ulumuddin.v10i1.379 Pengelola Web Kemdikbud. (n.d.). Surat Edaran Pencegahan Covid-19 pada Satuan Pendidikan. Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Purwanto, S. (2008). Pocket Manajemen Waktu. Esensi Erlangga Group. Rukajat, A. (2018). Pendekatan Penelitian Kuantitatif: Quantitative Research Approach. Deeppublish. Santoso, F. S. (2020). Masa Depan Pendidikan Hukum Islam Di Perguruan Tinggi Keagamaan Islam Refleksi Pembelajaran Di Masa Kedaruratan COVID-19. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 10(1), 13–26. https://doi.org/10.47200/ulumuddin.v10i1.378 Sinaga, O. S., Hasibuan, A., Efendi, E., Priyojadmiko, E., Butarbutar, M., Purba, S., Karwanto, Silalahi, M. A., Hidayatulloh, N., & Muliana. (2020). Manajemen Kinerja dalam Organisasi. Yayasan Kita Menulis. Sugiyono. (2012). Memahami Penelitian Kualitatif. Alfabeta. Sukmadinata, N. S. (2011). Metode Penelitian Pendidikan. Remaja Rosda Karya. Surur, A. M. (2017). Formasi 4-1-5 Penakhluk Masalah (Studi Kasus: Penulisan Karya Tulis Ilmiah Proposal Skripsi STAIN Kediri 2017). Prosiding Seminar Nasional PPKn III, 1–8. Ummasyroh, U., Fadila, D., & Herawati, Y. (2013). Efektifitas Manajemen Waktu Bagi Mahasiswa untuk Meningkatkan Target Akademis pada Politeknik Negeri Sriwijaya. Orasi Bisnis: Jurnal Ilmiah Administrasi Niaga, 9(3). Wiani, N. A. (2018). Konsep Manajemen PAUD Berdaya Saing. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 25–44.